The effectiveness of website-based drug information services by pharmaceutical personnel on medication adherence in hypertensive patients: A Study at Lumbung Community Health Center - Indriastuti, Marlina; Hani Fitriani; Muhammad Thesa Ghozali; Nisa Febrinasari; Muthia Dewi Marthilia Alim (Borobudur Pharmacy Review, 2026)
This study was motivated by the suboptimal medication adherence among patients with hypertension, which may affect the success of therapy. The aim of this study was to determine the effectiveness of a web-based educational application on medication adherence and to assess the differences in adherence levels before and after the intervention among hypertensive patients at Lumbung Community Health Center, Ciamis Regency. This research employed a quantitative approach with a pre-experimental one-group pretest–posttest design involving 57 respondents. Data were collected at Lumbung Community Health Center using questionnaires, and web-based educational interventions were provided in three stages with a three-day interval between each session. Medication adherence was measured before and after the educational intervention. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant improvement in medication adherence following the web-based educational intervention, with a significance value of p = 0.00001 (p < 0.05). These findings indicate a statistically significant difference in medication adherence levels before and after the web-based educational intervention.